Arthur, Clean Your Room! - Brown, Marc (Random House Group Ltd, 1999)
When Arthur's mother orders him to get rid of some of the old junk cluttering his room, Arthur decides to have a garage sale. But when his first customer, Buster, doesn't have enough money for the toy he wants, a trade is worked out. Soon word spreads that Arthur has great stuff to trade, and by the end of the day, Arthur has gotten rid of all his old junk. His mother is pleased, until she finds out that D.W. is in business too--renting out her room to store all of Arthur's new junk!
Keywords: Juvenile literature-English language-Fiction